Peran ekonomi islam: implementasi nilai-nilai al-qur’an dan hadis dalam pengembangan ekonomi di era globalisasi - Muchlisin, Yusuf Arif (Maliki Interdisciplinary Journal, 2026)
The implementation of the values of the Qur'an and Hadith in economic development is a step to integrate the principles of Islamic teachings into economic activities. The purpose of this study is to analyze how the values of the Qur'an and Hadith are implemented in economic development in the era of globalization, as well as their impact on economic growth and community welfare. The research method used is methodological, with the author collecting data from various sources, including previously published books and articles. Before choosing the topic to be discussed, the author read books, journals, and other relevant literature in accordance with the author's understanding. The results show that the implementation of the values of the Qur'an and Hadith in economic development in the era of globalization can help create an economic system that is more just, sustainable, and oriented towards the welfare of society. In the context of applying the principles of Islamic economics, this can also support the development of a more inclusive and sustainable Islamic economic sector. Although there are still some obstacles in applying the values of the Qur'an and Hadith in economic development, these efforts can make a positive contribution to economic growth in Indonesia.